Perancangan Alat Angkat (Dongkrat Bold) Elektrik - Anwar, Muh. Syahrul; Sisworo, Raden Rinova; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2022)
The jack is one of the modern technologies that is used to facilitate work during the process of lifting heavy loads so that heavy loads will be easily lifted according to the desired needs. The purpose of this research is to know the designer of the electric lift (bold jack) and to know the designer of the gearbox/gear holder and the motor mount. This research method design design, calculate the load, calculate the torque and power transmission, . In this study, it produces 5880 joules of work with a force of 14700 N, has a dc motor with 400 watts and a rotational speed of 700 rpm with power transmission that occurs ivn some parts of the motor at 700 rpm, reducer at 480 rpm, sprocket 345.6 rpm and what happens to the jack is 57.6 rpm with a chain speed of 1.645 m/s and the allowable shear stress is 0.00019 Mp and the equivalent load is 113.37 or 5142 kgf.Key words : Formulation, clove oil. engine performance